Enhance Skills and Utilization of The G-Form Application Among Elderly Health Cadres at Health-Post - Kusumaratna, Rina Kurniasri; Gunawan, Talitha Imanina Putri; Fahreza, Muhammad Abdul Hafiz; Wulandari, Utami (Universitas Malahayati Lampung, 2025)
ABSTRACT Elderly health cadres were community members who selflessly devoted their time and skills to serve as elderly posyandu cadres. Their essential contributions enhanced accessibility to health services for seniors and boosted community participation in health initiatives. The introduction of the simple early screening (SKILAS) instrument significantly improved the early detection of health issues among the elderly, ensuring timely care and intervention. Health education employed lectures, informational leaflets, and interactive video informative as primary media education, supplemented by home-visit observations to evaluate community service activities. After a two-day training session, twenty elderly health cadres significantly improved their skills in performing simple elderly screenings and effectively using the e-SKILAS form for early detection activities at the integrated health-post (p<0.001). To ensure they stayed informed about community health issues affecting the elderly, it was recommended that training sessions be conducted routinely on a biannual basis. Keywords: SKILAS Intrument, Early Detection, Elderly Heath, Community Cadres, Posyandu.